(untitled) (Journal of Information Systems and Technology Management, 2018)
The geographical, temporal distances and socio-cultural differences are the biggest challenges for Global Software Development (GSD). In GSD, it is necessary to deal with behaviors, values and skills of the team members, conflicts, rework, delays, etc. can influence a software production process. The objective of this paper is to identify the sociocultural aspects and propose a classification structure under different analytical perspectives in order to offer adequate support to the management of GSD teams. A systematic mapping and proposal an approach that classifies aspects in three perspectives: collaboration, people and external. The analysis allows the project manager to make decisions about the performance of human resources and mitigate problems arising from communication, cooperation and coordination, generating better results in indicators of productivity, quality and efficiency of GSD teams.